Sargassum fusiforme polysaccharide is a potential auxiliary substance for metformin in the management of diabetes. Issue 5 (23rd February 2022) - Wu, Juan; Jia, Rui-Bo; Luo, Donghui; Li, Zhao-Rong; Lin, Lianzhu; Zheng, Qianwen; Zhao, Mouming
Abstract : Study of the positive effects of LMET-SFP in high-fat diet and streptozotocin-induced diabetic rats, and the underlying mechanisms of LMET-SFP as compared to metformin alone in managing diabetes. Abstract : The present study investigated the positive effects of relatively low-dose metformin combined with Sargassum fusiforme polysaccharide (LMET-SFP) in high-fat diet and streptozotocin-induced diabetic rats, and explored the underlying mechanisms of LMET-SFP as compared to metformin alone in managing diabetes. The results indicate that both metformin and LMET-SFP can attenuate body weight loss and ameliorate hyperglycemia, insulin resistance and hyperlipidemia, and LMET-SFP exhibited better effects in lowering fasting blood glucose levels, insulin resistance index and serum cholesterol compared to metformin only. The administration of LMET-SFP could ameliorate liver dysfunction in diabetic rats. In addition, fecal bile acid data implied that LMET-SFP intervention contributed to an increase in fecal total bile acids, ursodesoxycholic acid and tauroursodesoxycholic acid profiles when compared to metformin treatment. Additionally, intestinal microbiological analysis showed that the acknowledged probiotics Lactobacillus and Bifidobacterium exhibited higher levels in the LMET-SFP group compared to the metformin group. RT-qPCR results demonstrated that the better hypoglycemic effects of LMET-SFP were mainly attributed to the down-regulation of 3-hydroxy-3-methylglutaryl-coenzyme A, cytosolic phosphoenolpyruvate carboxykinase and glucose-6-phosphatase expression, and the up-regulation of cholesterol 7α-hydroxylase expression, in contrast to metformin alone. These results suggest that SFP may be used as an auxiliary hypoglycemic substance for metformin in the future.